Anxiety Levels of Futsal Referees in the West Java Provincial Sports Week 2022 - Bangbang Syamsudar; Sumbara Hambal; Syahid Nuryasin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The aim of this research was to determine the level of anxiety among futsal referees officiating matches in the 14th West Java Provincial Sports Week 2022. The research method used a quantitative descriptive approach. Data collection was done using the Sport Competition Anxiety Test (SCAT) instrument distributed through Google Forms. The subjects of this study were futsal referees participating in the West Java Provincial Sports Week 2022, totaling 14 individuals. The research findings revealed that the level of anxiety among the referees fell into the low category at 20%, the moderate category at 73%, and the high category at 7%. This indicates that the majority (73%) of the futsal referees in the Provincial Sports Week experienced moderate anxiety. From these results, it can be inferred that the majority of the referees on duty had a moderate level of anxiety, which can be attributed to the certification level held by the referees, as 13 of them were nationally certified referees.